Analisis Angka Kecelakaan Kerja Dengan Metode Statistik Kecelakaan Kerja Di PT. XYZ - Aulia Agung Dermawan; Arrazy Elba Ridha; Dimas Akmarul Putera (Industrial Engineering, Engineering of Faculty, Universitas Kadiri, 2022)
PT XYZ is a company engaged in manufacturing and also one of the State-Owned Enterprises (BUMN) that produces urea and ammonia fertilizers. Work accidents that have occurred at PT XYZ in 2018-2019 are 9 cases of work accidents such as being sprayed with carbamate, hit by a hammer, hit by a splash of aqueous ammonia. The purpose of this study was to determine the level of frequency, severity and Safe-T-Score. In this study, the calculation of the number of work accidents used is the frequency of stating accidents that occur every 1,000,000 working hours, severity stating the loss of working days every 1,000,000 working hours, Safe T Score aims to compare the results of the frequency of accidents. From the results of the research, the frequency level in 2018 was 3.42 and 2019 was 1.05 accidents every 1,000. 000 working hours so the frequency of accidents is getting lower from year to year. The severity level in 2018-2019 is 0 days, this is because PT XYZ has never experienced a work accident that has eliminated working hours. The 2019 Safe-T-Score result is -1763.07, this indicates that the frequency of work accidents shows an improving condition from the previous year.PT XYZ adalah salah satu Badan Usaha Milik Negara (BUMN) yang memproduksi pupuk urea dan amonia. Kecelakaan kerja yang pernah terjadi pada tahun 2018-2019 ialah 9 kasus kecelakaan kerja seperti Tersembur karbamat, terkena martil, terkena percikan aquos ammonia. Tujuan dari penelitian ini adalah untuk mengetahui tingkat frekuensi, severity dan Safe-T-Score. Dalam penelitian ini perhitungan angka kecelakaan kerja yang di gunakan adalah frekuensi menyatakan kecelakaan yang terjadi setiap 1.000.000 jam kerja, severity menyatakan hilangnya hari kerja setiap 1.000.000 jam kerja, Safe T Score bertujuan membandingkan hasil tingkat frekuensi kecelakaan. Dari hasil penelitian tingkat frekuensi tahun 2018 adalah 3,42 dan 2019 adalah 1,05 kali terjadi kecelakaan setiap 1.000.000 jam kerja jadi frekuensi kecelakaan semakin rendah dari tahun ke tahun. Tingkat severity pada tahun 2018-2019 adalah 0 hari, Hal ini di karenakan PT XYZ tidak pernah mengalami kecelakaan kerja yang sampai menghilangkan jam kerja. Hasil Safe-T-Score tahun 2019 adalah -1763,07 hal ini menunjukkan bahwa frekuensi kecelakaan kerja menunjukkan keadaan yang membaik dari tahun sebelumnya.